Double Cystic Duct as Rare Anatomic Variant - Antonio Valero-Liñán; Toni Stoyanov; Alba Sanchez-Gallego; Elias Garcia-Grimaldo; José Gonzalez-Masiá; José Ignacio Miota De Llama (Journal of Biomedical & Clinical Research)
The variations of the cystic duct are so common that only 30% of all humans present the classical anatomical arrangement between the common bile duct (CBD), the cystic duct, and adjacent arteries. Thus, it could be considered that anomalies of the biliary tree are a rule rather than an exception. Duplication of the cystic duct, however, is a very uncommon anatomical finding. In the Department of General and Digestive Surgery of the University Hospital Complex Albacete, a 73-year-old patient was admitted with symptoms of cholangitis. He underwent emergency surgery that found exacerbated chronic cholecystitis and dilation of the CBD. Cholecystectomy was performed with identification of a double cystic duct that drained separately in the CBD and exploration of the last revealed cholangitis without choledocholithiasis. The postoperative period progressed favourably, proceeding to discharge from the hospital with Kehr drainage closed. In conclusion, we consider that the routine use of intraoperative cholangiography when there is suspicion of anatomical variations of the biliary tree is mandatory to rule out lesions or alterations thereof.